2020
DOI: 10.1096/fj.201903263rrr
|View full text |Cite
|
Sign up to set email alerts
|

A highly efficient hybrid peptide ameliorates intestinal inflammation and mucosal barrier damage by neutralizing lipopolysaccharides and antagonizing the lipopolysaccharide‐receptor interaction

Abstract: Intestinal inflammatory disorders, such as inflammatory bowel disease, are major contributors to mortality and morbidity in humans and animals worldwide. While some native peptides have great potential as therapeutic agents against intestinal inflammation, potential cytotoxicity, anti-inciting action, and suppression of antiinflammatory activity may limit their development as anti-inflammatory agents. Peptide hybridization is an effective approach for the design and engineering of novel functional peptides bec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 115 publications
(293 reference statements)
0
7
0
Order By: Relevance
“…LPS is a strong pro‐inflammatory factor that may be closely related to the occurrence and development of UC (Rosillo et al, 2015). Studies also confirmed that LPS can induce RAW 264.7 cells to secrete pro‐inflammatory cytokines (Hwang et al, 2016), thereby destroying the intestinal mucosal barrier, and ultimately leading to the continuous development of inflammation (Wei et al, 2020). Based on the above studies, we investigated the effect of HSYA on DSS‐induced UC in rats and LPS–induced UC in RAW 264.7 cells.…”
Section: Discussionmentioning
confidence: 88%
“…LPS is a strong pro‐inflammatory factor that may be closely related to the occurrence and development of UC (Rosillo et al, 2015). Studies also confirmed that LPS can induce RAW 264.7 cells to secrete pro‐inflammatory cytokines (Hwang et al, 2016), thereby destroying the intestinal mucosal barrier, and ultimately leading to the continuous development of inflammation (Wei et al, 2020). Based on the above studies, we investigated the effect of HSYA on DSS‐induced UC in rats and LPS–induced UC in RAW 264.7 cells.…”
Section: Discussionmentioning
confidence: 88%
“…Another hybrid peptide containing the functional core region of LL-37 was evaluated by Wei et al [ 11 ], this time hybridized with the active center of cecropin A (C), called peptide C-L. This hybrid also exerted a protective effect against LPS-induced intestinal inflammation, protecting the intestinal tissue from damage by reducing leukocyte infiltration, inflammatory cytokine concentrations and cell apoptosis.…”
Section: Discussionmentioning
confidence: 99%
“…Several preclinical studies with models of intestinal inflammation aimed to understand the mechanisms of action of these anti-inflammatory proteins and peptides that reduce TNF-α. Such studies describe the mechanisms involved in the action of these molecules to develop the best strategies for treating these diseases [10][11][12]. Therefore, this systematic review aimed to study the mechanisms of action of these proteins and peptides and their effects on the inflamed intestinal barrier in animal models.…”
Section: Introductionmentioning
confidence: 99%
“…The LPS-induced macrophage RAW264.7 inflammatory model is commonly used to detect the anti-inflammatory activity of natural drugs [28,29]. RWA264.7 cells are also being used to research gastrointestinal mucosal damage and anti-inflammation mechanisms [30,31].…”
Section: Discussionmentioning
confidence: 99%